2006
DOI: 10.1177/1358863x06072213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute exercise on endothelial progenitor cells in patients with peripheral arterial disease

Abstract: Abstract:To determine whether exercise increases endothelial progenitor cells (EPCs) in patients with peripheral vascular disease, we developed a multi-parameter flow cytometry assay to rigorously assess EPCs and mature endothelial cells (ECs) in control subjects and patients with peripheral artery disease (PAD) subjected to graded exercise. Blood was collected from young healthy subjects (n ϭ 9, mean age 33 years), older healthy subjects (n ϭ 13, mean age 66 years), and older subjects with PAD (n ϭ 15, mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 44 publications
(52 reference statements)
4
49
2
Order By: Relevance
“…Indeed, while there was a numerical exercise-induced increase in CD34ϩ cell number across groups, there was no statistically significant mobilization of CD34ϩ cells in any group. This finding is consistent with three other reports in healthy young (35) and older adults (29,34); however, in the latter study (29), exercise did mobilize CD34ϩ cells in healthy young adults, indicating a possible effect of age on CD34ϩ cell mobilization when young and older adults were directly compared.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, while there was a numerical exercise-induced increase in CD34ϩ cell number across groups, there was no statistically significant mobilization of CD34ϩ cells in any group. This finding is consistent with three other reports in healthy young (35) and older adults (29,34); however, in the latter study (29), exercise did mobilize CD34ϩ cells in healthy young adults, indicating a possible effect of age on CD34ϩ cell mobilization when young and older adults were directly compared.…”
Section: Discussionsupporting
confidence: 93%
“…141,142 Other authors showed exercise-related EPC increase also in the absence of ischemia. 143,144 Prolonged strenuous exercise (half-marathon, marathon, or spartathlon), however, showed no change or a significant increase in circulating progenitor cells. [145][146][147][148] The principal mechanism of EPC mobilization from the bone marrow seems to depend on the activation of eNOS in the presence of several mobilizing factors such as VEGF 149 or placental growth factor.…”
Section: No Generation In the Endotheliummentioning
confidence: 96%
“…While studying a group of healthy young subjects, a group of healthy old and a group of patients with PAD after an acute exercise session, Shaffer et al [130] concluded that young healthy individuals have an increased capacity to mobilize EPCs, as compared with older individuals. Interestingly, patients with PAD appeared to be unable to mount a significant increase in circulating EPCs, despite the ischemic stimulus.…”
Section: Effect Of Acute Exercise On Epcsmentioning
confidence: 99%